Tajemnicze Nazaret – na styku historii i Biblii - Baraniak, Marek (Colloquia Litteraria, 2023)
The biblical Nazareth is chronologically the first important element of the historical picture of Jesus, the credibility of which is constantly being questioned. The discussion around it carries a trace of debate between minimalists and maximalists. The presented outline of a holistic picture of the history of this settlement, which consists of information and conclusions obtained on the basis of archaeological and historical-literary research in confrontation with the evidence of religious tradition expressed in sacred architecture, facilitates a critical assessment of the credibility of this place.